Phospholipases and Reactive Oxygen Species Derived Lipid Biomarkers in Healthy and Diseased Humans and Animals – A Focus on Lysophosphatidylcholine - Engel, Kathrin M.; Schiller, Jürgen; Galuska, Christina E.; Fuchs, Beate (Frontiers in Physiology, 2021)
Phospholipids are converted into lipid biomarkers by the action of phospholipases and reactive oxygen species, which are activated or released under certain physiological and pathophysiological conditions. Therefore, the in vivo concentration of such lipid biomarkers (e.g. lysophospholipids) is altered in humans and animals under different conditions such as inflammation, stress, medication and nutrition. Lysophospholipids are particularly interesting because they are known to possess pro- and anti-inflammatory properties and may be generated by two different pathways: either by the influence of phospholipase A2 or by different reactive oxygen species that are generated in significant amounts under inflammatory conditions. Both lead to the cleavage of unsaturated acyl residues. This review provides a short summary of the mechanisms by which lipid biomarkers are generated under in vitro and in vivo conditions. The focus will be on lysophosphatidylcholine because usually, this is the lysophospholipid species which occurs in the highest concentration and is, thus, easily detectable by chromatographic and spectroscopic methods. Finally, the effects of lipid biomarkers as signaling molecules and their roles in different human and animal pathologies such as infertility, cancer, atherosclerosis and aging will be shortly discussed.